Evaluasi Teknis dan Ekonomi Geomteri Peledakan Terhadap Fragmentasi Batu Andesit dan Biaya Peledakan PT. Atika Tunggal Mandiri, Nagari Manggilang, Kecamatan Pangkalan Koto Baru, Kabupaten Lima Puluh Kota, Provinsi Sumatera Barat - Ade Muthia Febriyanti; Rizto Salia Zakri (Departemen Teknik Pertambangan FT UNP, 2023)
From the results of observations at PT. Atika Tunggal Mandiri saw a lot of fragmentation resulting from blasting which produced boulder. The results of blasting based on company standards is 80% with a size of 50 cm. So, the percentage of boulder that can be tolerated by the company is only ± 20%. Meanwhile, from the observation results, it was found that from blasting activities in the field, 45.28% boulder was obtained. So, the results of blasting in the field still produce boulder in excess of the desired amount. The objective of this research is to obtain the results of comparison of actual fragmentation and R.L Ash, as well as actual and proposed blasting costs. The research method is the calculation of R.L. Ash and blasting test results in the field with 40 trial holes using the splitdesktop software method. Tests carried out in the field with the calculation of the theory of R. L. Ash 40 blast holes obtained the percentage of fragmentation size >50 cm at 2.34% which was retained (boulder) and escaped by 97.66%. The results can be used as a reference for companies to consider evaluating and analyzing blast geometry. The results of the analysis of aqueous blasting costs Rp. 8,137,59 /ton, the geometric blasting cost proposed by R. L. Ash theory is Rp. 9,474,79 /ton, and the geometric blasting cost of Proposed C. J. Konya is Rp. 9,890,17 /ton. The author prefers the proposed blasting geometry according to Geometry R. L. Ash to be tested in the field because the Powder Factor value is smaller and better because the Powder Factor value is smaller.